Contemporary Nordic Literature and Spatiality (Springer Nature, 2021)
This open access collection offers a detailed mapping of recent Nordic literature and its different genres (fiction, poetry, and children’s literature) through the perspective of spatiality. Concentrating on contemporary Nordic literature, the book presents a distinctive view on the spatial turn and widens the understanding of Nordic literature outside of canonized authors. Examining literatures by Danish, Norwegian, Swedish, and Finnish authors, the chapters investigate a recurrent theme of social criticism and analyze this criticism against the welfare state and power hierarchies in spatial terms. The chapters explore various narrative worlds and spaces—from the urban to parks and forests, from textual spaces to spatial thematics, studying these spatial features in relation to the problems of late modernity.